2009
DOI: 10.1182/blood-2008-07-169359
|View full text |Cite
|
Sign up to set email alerts
|

The distal carboxyl-terminal domains of ADAMTS13 are required for regulation of in vivo thrombus formation

Abstract: ADAMTS13 is a multidomain protease that limits platelet thrombogenesis through the cleavage of von Willebrand factor (VWF). We previously identified 2 types of mouse Adamts13 gene: the 129/Sv-strain Adamts13 gene encodes the long-form ADAMTS13 having the same domains as human ADAMTS13, whereas the C57BL/6-strain Adamts13 gene encodes the short-form ADAMTS13 lacking the distal C-terminal domains. To assess the physiologic significance of the distal C-terminal domains of ADAMTS13, we generated and analyzed 129/S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 38 publications
2
75
0
Order By: Relevance
“…Several studies have shown that the carboxy-terminal TSP2-8 and CUB1-2 domains are important for the processing of VWF by ADAMTS13. 22,30,31 Zheng and coworkers showed that platelet counts on admission were lower in patients with anti-TSP2-8 and/or anti-CUB1-2 IgG. 19 This observation suggests that antibodies directed towards the carboxy-terminal domains inhibit ADAMTS13 activity or alternatively enhance its clearance from the circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the carboxy-terminal TSP2-8 and CUB1-2 domains are important for the processing of VWF by ADAMTS13. 22,30,31 Zheng and coworkers showed that platelet counts on admission were lower in patients with anti-TSP2-8 and/or anti-CUB1-2 IgG. 19 This observation suggests that antibodies directed towards the carboxy-terminal domains inhibit ADAMTS13 activity or alternatively enhance its clearance from the circulation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Banno et al 42 have reported that a naturally occurring mutation in certain strains of mice that truncates murine ADATMS13 after the sixth TSP1 repeat results in significantly reduced efficacy for systemic antithrombosis. 42 A deletion mutation in the TSP1 sixth repeat of ADAMTS13 was identified in a family with hereditary TTP.…”
Section: Discussionmentioning
confidence: 99%
“…35 Although similar activity is observed in static assays, this truncated ADAMTS13 demonstrates increased thrombotic occlusions under shear stress conditions, because it is not fully active in vivo. 36 To mitigate any artifacts caused by these differences, we digested both human and mouse substrates with their respective species-specific ADAMTS13. In addition, we performed coinjections of full-length mouse Adamts13 cDNA with the Vwf cDNAs to observe any influences on the VWF multimer profile or clearance rate in vivo.…”
Section: Discussionmentioning
confidence: 99%